Right atrial mechanics by strain echocardiography in chronic thromboembolic pulmonary hypertension. (25th November 2020) - Ferreira Fonseca, M; Baptista, R; Samouco, G; Soeiro, P; Martins, R; Castro, G; Goncalves, L
Abstract: Introduction: Chronic thromboembolic pulmonary hypertension (CPTEH) is the result of thromboemboli leading not only to mechanical obstruction but also pulmonary vascular remodelling and progressive increase in right heart afterload. Prognostic assessment in CPTEH is complex and multifactorial. Purpose: We used two-dimensional strain echocardiography (2D-STE) to quantify right atrial (RA) mechanics and its correlation with invasive hemodynamics, load-dependent biomarkers and well-known prognostic markers in patients with CTEPH. Methods: A total of 44 patients (24 females, mean age 61±15.6 years) with CTEPH were recruited. 2D-STE was used to measure right atrial reservoir strain (RASr) (Figure 1) which was then compared to conventional ultrasound measurements, right heart catheterisation (RHC) measurements, the percentage of obstruction in ventilation-perfusion pulmonary single-photon emission computed tomography (V/Q SPECT), B-type natriuretic peptide (BNP) values and 6-minute walk test (6MWT) performance. All patients underwent transthoracic echocardiographic evaluation with a maximal time distance of three months to RHC. Results: There was a significant positive correlation of RASr with RV longitudinal function determined by tricuspid annular plane systolic excursion (TAPSE) (r=0.488, p=0.003), tricuspid annular peak systolic velocity (S') (r=0.490, p=0.002), right ventricular outflow tract velocity time integral (RVOT VTI) (r=0.457, p=0.005), as well as with 6MWT (r=0.491, p=0.004). There was a significant negative correlation of RASr with mean pulmonary artery pressure (r=−0.513, p=0.002), pulmonary vascular resistance (r=−0.439, p=0.011) and right atrial pressure (RAP) (r=−0.513, p=0.002). RASr was also correlated with Log-transformed BNP values (r=−0.552, p<0, 001), and in a multivariate linear regression model, RASr was an independent predictor of Log-transformed BNP values (β=−0.448, 95% CI: −0.046 to −0.009; p=0.005). There was no correlation between RASr and the percentage of obstruction in V/Q SPECT (r=0.164, p=0.388). Conclusion: 2D-STE-derived RA mechanics demonstrated to be a useful, non-invasive, surrogate measurement of RHC parameters. It also predicted important clinical/laboratory prognostic measurements, such as BNP and 6MWT performance. The absence of correlation between 2D-STE values and the percentage of vessel obstruction determined by SPECT may suggest that RV maladaptive response to the obstruction, rather than the degree of obstruction, dictates right heart failure in CTEPH. Funding Acknowledgement: Type of funding source: None